Genetic diversity of sago palm (metroxyon sagu rottb.) in Mindanao and its phylogenetic position within the arecaceae family based on RPII gene sequences - Adtoon, Jonah A. (2009)
Taxonomic classification among sago palms, Metroxylon sagu Rottb. is still ambivalent. In order to elucidate this controversy, this study was done to detect variation among m.sagu samples in Mindanao using RAPD analysis of long and short primers and RPBII gene sequence, clarify the taxonomic classification of different morphotypes of the palm using gene sequences and determine the placement of M. sagu on the Family Arecaccae. There were seven morphotypes of sago palms found in Mindanao, two of which are spiny and five are spineless. They were then characterized according to their morphological band pattern on the petiole and rachis which are very spiny, the green and white bands, for spineless these are brown, weak black, 3 brown bands, striped brown and white and gray bands. In the sample screening for best representatives, short and long RAPD primers were used. The genetic variation detected in short primers were 0.51% to 12.46% while for long primers genetic variation ranged from 1.59% to 22.12%. long RAPD primers are more useful in determining genetic variation among samples because the stricter conditions of hormology for the priming sites enables them to detect more mutations. Intron 23 of RPBII gene was isolated to determine its sequence data, the isolated fragment was approximately 600 bp in size, smaller than those of other species. The aligned DNA sequences have a total length of 519 bp although the original length of the DNA sequences ranged from 556 to 629 bp. There were four base substitutions in the aligned sequences of 14 samples, all are transversions. Almost all samples yielded nil genetic variation. Using Neighbor Joining and Maximum Likelihood, the analysis of 14 samples with C. nana as an outgroup, showed that all sago morphotypes belong to one species taxa. Metroxylon sagu Rottb. All the phylogenetic trees generated based on Neighbor Joining and Maximum Likelihood methods have similar topology, with high bootstrap support that concluded the affirmation of the membership of M. sagu to the subfamily Calamoideae